The Theological Value of Al-Ma’un in Free Lunch Policy: An Islamic Ethical Perspective on Social Empowerment - Zuhdi, Andifa Nurasyam (Jurnal Muhammadiyah Studies, 2024)
Providing free lunches is one of the innovations to prepare Indonesia's golden generation. This policy focuses on improving the nutrition of children and pregnant women. By providing free lunches, it is hoped that it will have a domino effect on the community. Of course, this policy must also be based on the ethics that apply in Indonesia. The free lunch policy has also gone through a series of in-depth scientific studies. Of course, this research will have a significant positive impact on society, considering that there is still a lot of inequality and poverty in Indonesia. Programs that are classified as social policies in economics are usually called "Robin Hood" policies. Considering this big policy, it is hoped that there will be even and special support for people who need it. The government also needs to develop a powerful formula so that this policy can be realized and evenly distributed, especially in remote and underdeveloped areas in Indonesia. Of course, the main goal of a free lunch policy is to effectively reduce inequality and promote a fair allocation of economic resources.